Pelatihan Dasar Microsoft Office Pada SMK Bintang Nusantara - Okta Irawati; Iis Istiqomah; Sutrisno (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Vocational high school (SMK) is one of the vocational education programs that has received attention from the government. Various programs that have been launched by the government aim to produce competent graduates who can meet industry needs. For graduates who wish to develop careers in the office sector, they should master the applications used in offices. The application that needs to be mastered is Microsoft Office. To achieve this, the education and learning process must refer to and be in accordance with the applicable curriculum in accordance with the vision, mission and goals of the school. The alignment of the SMK education curriculum with the world of work has been designed from the start, one of which is through the "link and match" program so that the curriculum between SMK and the industrial world is compatible. For this reason, SMK graduates are expected to be immediately absorbed in the world of work. In addition, when they graduate, SMK students are also equipped with competency certification as proof that they have competence in that field. Thus, these SMK graduates have a greater chance of being accepted in the industry compared to general school graduates. For graduates who wish to develop careers in the office sector, they should master the applications used in offices. The application that needs to be mastered is Microsoft Office. The advantage of mastering Microsoft Office applications is that graduates can immediately work as data entry. Currently, expertise in mastering computer technology is a must for office and industrial players. The purpose of implementing this PKM is to organize Microsoft Office training for office needs for Bintang Nusantara Vocational High School students. From the results of the training it can be seen that 75 percent of the participants already know the functions of Microsoft Word for office basics. The training participants were very enthusiastic about participating in all the series of events. This can be seen from their seriousness in practicing the module guided by the speaker.